2015-12-31 Effective public leadership to drive organisational change in the public health sector in order to improve service delivery : the case of the Western Cape Department of Health - Isaacs, Rafeeqah (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.